Penguatan Literasi Perpajakan bagi Peserta Didik di Sekolah Menengah Atas sebagai upaya Fiskal dalam meningkatkan Kesadaran Wajib Pajak sejak Dini - Karmilah, Karmilah; Abhull Azwad, Nugraha; Ashari, Yuli; Fatimah, Sitti (Journal Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
The level of tax literacy among students remains relatively low, even though early understanding of taxation is a crucial foundation for shaping aware and compliant taxpayers in the future. This community service program aims to enhance the understanding of taxation among Senior High School (SMA) students through an interactive and practical educational approach. The implementation methods included socialization, workshops, role-playing simulations, and tax case discussions designed to foster students' interest and comprehension of the function of taxes in national development. The results of the program showed a significant increase in students’ enthusiasm and understanding of basic tax concepts, tax administration, and their implications for public welfare. Positive responses from schools further indicated the potential sustainability of this program as part of a financial literacy extracurricular activity. Collaboration between universities, schools, and tax authorities is a strategic step to sustainably strengthen tax awareness among the younger generation.